2019
DOI: 10.15655/mw/2019/v10i3/49690
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Youth, Social Media Following, and Natural Disasters: What Matters Most to Them?

Abstract: This study attempted to understand youth's social media following during natural disasters. It investigated Malaysian youth's perception about the importance of immediacy, trust, and accuracy of social media news and information during natural disasters. This study found that youth prefer to consume social media news and information during natural disasters such as flooding, landslides, and haze. This is mainly contributed by the immediacy of news and information on social media. Besides immediacy, youth also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In concluding remark it can be said that Al Jazeera English, BBC News, and CNN are the mainstream news organizations followed by 94 million followers (to date) in their official Facebook pages. As the young generation follows news sources from their social media (Ismail et al, 2019; Shehata & Strömbäck, 2021), the news organizations are also interested to share news on their social media platform, Facebook.…”
Section: Discussionmentioning
confidence: 99%
“…In concluding remark it can be said that Al Jazeera English, BBC News, and CNN are the mainstream news organizations followed by 94 million followers (to date) in their official Facebook pages. As the young generation follows news sources from their social media (Ismail et al, 2019; Shehata & Strömbäck, 2021), the news organizations are also interested to share news on their social media platform, Facebook.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, vertical media is experiencing a rapid decline in social media platforms' growth (Robinson, 2019). Ismail, Ahmad, Noor, and Saw (2019) mentioned that around 80 per cent of Malaysian youth utilize social media, such as Facebook, WhatsApp, Twitter, and Instagram, to consume news and share opinions. Many newspapers cut editorial content and sack staff because of plunging circulation and falling ad revenues (Bassey, 2006).…”
Section: Social Mediamentioning
confidence: 99%
“…The earlier studies showed that social media has a role in promoting shisha smoking behavior which could negatively influence the public (Allem et al, 2018). Social media is often associated with youth, as they make the highest percentage of users (Greenhow et al, 2017;Ismail et al, 2019Ismail et al, , 2022. Ilakkuvan et al (2019) added, youth are frequent users of social media as it was reported that, 88% of those between the ages of 18-29 use the platform every day.…”
Section: Social Media and Shisha Smokingmentioning
confidence: 99%